Weakly periodic Gibbs measures of the ising model on the cayley tree of order five and six - Ganikhodjaev, Nasir; Rakhmattullaev, Muzaffar; Rodzhan, Mohd Hirzie (Springer Netherlands, 2018)
For Ising model on the Cayley tree of order five and six we present new weakly periodic (non-periodic) Gibbs measures corresponding to normal subgroups of indices two in the group representation of the Cayley tree.